World Cups impact analysis in the soccer players transaction and soccer globalization using complex network techniques - Alves, Antônio P. S.; Felix, Lucas G. da S.; do Carmo, Vitor E.; Barbosa, Carlos M.; da F. Vieira, Vinícius; Xavier, Carolina R. (Journal of Information and Data Management, 2019)
In this paper, we propose an analysis of the relationship between World Cup results and the number of transfers of soccer players of their national teams. For this study, networks are collected, modeled and generated for periods of time before each world cup since 1966. The effects of these events were evaluated by investigating the best and worst teams transfers networks, at each edition of the cups. We also investigated sociological theories that associate globalization to transfer networks in soccer, being able to show through quantitative data, the hypotheses raised and to renew these proposals showing the rise of new markets, such as those from Asia. To carry out the analysis, complex networks and data mining techniques were combined and this evaluation showed that countries that perform many transactions do not necessarily perform well in the world cups. However, part of the countries involved in numerous transfers can have a good performance, standing in good positions after the world cups.